Transgenic Crop Plants Volume 2: Utilization and Biosafety - Kole, Chittaranjan; Michler, Charles; Abbott, Albert G.; Hall, Timothy C. (Springer Berlin Heidelberg : Imprint: Springer, 2010)
Development of transgenic crop plants, their utilization for improved agriculture, health, ecology and environment and their socio-political impacts are currently important fields in education, research and industries and also of interest to policy makers, social activists and regulatory and funding agencies. This work prepared with a class-room approach on this multidisciplinary subject will fill an existing gap and meet the requirements of such a broad section of readers. Volume 2 with 13 chapters contributed by 41 eminent scientists from nine countries deliberates on the utilization of transgenic crops for resistance to herbicides, biotic stress and abiotic stress, manipulation of developmental traits, production of biofuel, biopharmaceuticals and algal bioproducts, amelioration of ecology and environment and fostering functional genomics as well as on regulations and steps for commercialization, patent and IPR issues, and compliance to concerns and compulsions of utilizing transgenic plants.